Balance in Virtual Reality: Effect of Age and Bilateral Vestibular Loss - Chiarovano, Elodie; Wang, Wei; Rogers, Stephen J.; MacDougall, Hamish G.; Curthoys, Ian S.; de Waele, Catherine (Frontiers in Neurology, 2017)
Background Quantitative balance measurement is used in clinical practice in order to prevent falls. The conditions of the test were limited to eyes open, eyes closed, and sway-referenced vision. We developed a new visual perturbation to challenge balance using virtual reality, measuring postural stability by a Wii Balance Board. Methods In this study, we recorded balance performance of 116 healthy subjects and of 10 bilateral vestibular loss patients using virtual reality in order to assess the effect of age and the effect of total loss of vestibular function. We used several conditions: eyes open (normal visual inputs), eyes closed (no visual inputs), stable visual world (vision referenced), and perturbed visual world (visual perturbation) at different amplitudes of perturbation. Balance under these visual conditions was assessed on the Wii Balance Board (WBB, stable support surface) and on the WBB plus foam rubber (unstable support surface). Results In healthy subjects, we found that the percentage of falls increased with age and with the amplitude of perturbation for both conditions: WBB or WBB+foam. Moreover, we can define a threshold for falls in each age group as the amplitude of perturbation which induced falls. For bilateral vestibular loss patients, on the WBB+foam, all of them failed with eyes closed and with perturbed visual world even at the minimal amplitude of perturbation. Finally, we observed that stable visual world induced fewer falls than eyes closed whatever the subject’s group (healthy or bilateral vestibular loss) and whatever the age decade. Conclusion Virtual reality allowed us to develop a useful new tool with a wide range of visual perturbations. Rather than only two levels of visual condition (eyes open and eyes closed), the virtual reality stimulus can be continuously adjusted to produce a visual perturbation powerful enough to induce falls even in young healthy subjects and which has allowed us to determine a threshold for falls.